Pembelajaran Ayat-ayat Kawnīyah di SMA Trensains 2 Pesantren Tebuireng Jombang - Muslih Muslih (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2018)
This research focuses on the implementation of teaching religion and science in “Trensains” Senior High School at Tebuireng Islamic Boarding School 2. This research concludes that the implementation of the integration of religion and science is summarized in a notion of “Trensains” that makes the Qur'ān the basis of construction of science by Agus Purwanto and Salahuddin Wahid. The implementation of such an integration can be categorized into three dimensions, namely ontological, epistemological, and axiological. In addition, the “Trensains” result in the integration of institutions, the integration of the curriculum, and the integration of learning process in the classroom, outside, and integration in daily activities. The problem experienced in learning includes the prevalence of dichotomy among educators, and the various abilities of learners. The facilities of learning are not yet complete, and funds are limited. The solution is to strengthen the understanding of the concept of integration of science in all elements in the form of manual integration for educator and learners, and to optimize the performance of educators and guidance and counseling, effective educators in planning learning by doing training preparation of learning plan, to optimize the use of existing facilities, and to maximize the role of the education board and the school committee in order to establish cooperation with stakeholder, agencies, government, or other communities in an effort to improve the quality of the school.